Effect of Caesarean Section on Neonatal Health in Bangladesh after Controlling Selection Bias: Propensity Score Based Analysis (Dhaka University Journal of Science, 2021)
The paper examines the effect of caesarean section (C-section) on early neonatal mortality, neonatal mortality, and early initiation of breastfeeding using Bangladesh Demographic and Health Survey (BDHS), 2014 data. Propensity score matching and weighting methods were used to estimate unbiased estimate of treatment effect. The study demonstrates how conclusion about treatment effect varies with and without having balance in the treatment groups. Standard analysis, without caring about balance, reveals that C-section has no significant impact on early neonatal mortality and neonatal mortality. After applying propensity score adjusted methods, balance was achieved in the treatment groups and it was found that C-section has significant effect on early neonatal mortality and neonatal mortality. However, there was no difference between standard and PS adjusted methods in estimating the effect of C-section on early initiation of breastfeeding. It is concluded that children who were delivered by C-section have significantly lower odds of early neonatal mortality, neonatal mortality, and early initiation of breastfeeding as compared to the children who were not delivered by C-section.Dhaka Univ. J. Sci. 69(1): 23-29, 2021 (January)